FIFA 11+ Kids dapat Meningkatkan Kekuatan Otot: Sebuah Perlakuan Selama 12 Minggu - Anam, Khoiril; Sumartiningsih, Sri; Fajar Widya Permana, Dhias; Nurfadhila, Risti; Ayu Aditia, Eva (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
This study aims to determine the application of the FIFA 11+ Kids program to increase muscle strength in children aged 11-12 years. This research uses experimental research with a pretest-posttest control group design. Twenty people were sampled in this study, divided into two groups: the treatment group and the control group. Purposive sampling was used in determining the research sample. The subject matching A-B-B-A technique was used to divide the treatment group and the control group. The instrument in this study is to measure arm muscle strength using a push-up test, measure leg muscle strength using a leg dynamometer test, and measure abdominal muscle strength using a sit-up test. Data analysis in this study used a paired sample t-test with a significance level of 5%. The results of the study in the treatment group showed a significance value of 0.000 (p<0.05), a significant value of leg strength was 0.004 (p<0.05), while a significant value of abdominal strength was 0.000 (p<0.05). Coaches and athletes can use the implications of this research as an injury prevention method for child footballers.